Perennial ryegrass infected with AR37 endophyte reduces survival of porina larvae - Jensen, J.G.; Popay, A.J. (New Zealand Plant Protection, 2004)
Two pot experiments were conducted to assess the impact of perennial ryegrass (Lolium perenne) infected with AR37 a novel strain of the endophytic fungus Neotyphodium lolii on porina (Wiseana cervinata) larvae The wildtype (WT) endophyte a commercially available novel endophyte strain named AR1 and Nil endophyte ryegrass were also tested Larval survival was reduced by AR37 in both experiments and by WT in one experiment Larval weights and head widths and tiller damage were also reduced by AR37 and to a lesser extent by WT Shortterm bioassays with excised tillers showed that W cervinata were slightly deterred from feeding on AR37 but only when offered a choice between AR37 and Nil No preference was shown between Nil and WT No effects of AR1 on W cervinata were observed